PENGARUH DAY OF THE WEEK EFFECT TERHADA RETURN SAHAM PADA PERUSAHAAN YANG TERGABUNG DALAM JAKARTA ISLAMIC INDEX (JII) - Iswadi, Iswadi; Hafni, Nurul (Jurnal Akuntansi dan Keuangan, 2018)
This study aims to examine the effect of day of the week effect on the stock returns in the Jakarta Islamic Index (JII) in the period Desember 2017-May 2017. The data used in this study are secondary data obtained from www.yahoo.finance.com. The sample in this study are all compinies incorporated in the Jakarta Islamic Index as many as 30 companies. This study used multiple linear regression tests with dummy variables. The results of the study partially indicateÂ  that trading days on Thursday sifnificantly influence JII stock returns which can be seen from a significant value of 0,009. So, it can be concluded that day of the week effect on stock return in the jakarta islamic index (JII).